Handling Pattern of Pesticides in Vegetables: A Case Study of Bhaktapur - Budhathoki, Naba Raj; Acharya, Pushpa Raj; Karki, Dhruva (Journal of Science and Engineering, 2019)
This research work explores handling practices of pesticides used in vegetables on the part of farmers in Bhaktapur. Specifically, it attempts to investigate the contribution of pesticides applicators to overall mishandling of pesticides. Data for this work were collected in 2018 from four locations of Bhaktapur. Primary data were collected from 123 vegetable farmers and direct observation of 42 vegetable farms based in the selected zones using questionnaire. Discussions with experts and pilot study with farmers were conducted to improve the questionnaire and provide factual data. Frequency distributions, Means, Chi-square tests were utilised for data analysis. The results of the study show that vegetable farmers were applying pesticides, without caring much about the others, in vegetable production. They frequently depended upon local sellers and neighbours to choose the best pesticide to apply. On average, pesticide handling practices at any point seemed inappropriate. Factors that influence farmers' handling practices include education, training and practical consciousness. The study indicated that vegetable farm women have higher level of exposure of pesticide risking a long term health impacts. The results of the study underscore the need of educational interventions for promoting safety during each step of pesticide handling and the responsibility of the farmers towards the society.